Quotas in Egypt: Understanding the Implementation and Discourse about Introducing Quotas for Women in the People’s Assembly between Women’s Groups, Members of Parliament and Political Parties from 2005-2012 - Belle-Isle, Kristen Anne (AUC Knowledge Fountain, 2014)
Quotas for women in Egypt are controversial. The debate about quotas began in the 1970s and has exploded into current debates since January 25th, 2011. Quotas are one vehicle of increasing women’s political representation that became popular after the Beijing Platform for Acton was announced in 1995. This research examines why certain actors in Egypt called for the use of a quota for women at the national level in Egypt. I consider this question in the last few years of Hosni Mubarak’s rule and in the post-Mubarak transitional phase that began in February 2011. I examine the time frame in which Egypt considers using quotas for women and the impact international legislation has on Egyptian lawmakers. This research looks beyond using quotas to quantitatively add women to Egyptian national Parliament to address their experiences and goals as a Member of Parliament. This project engages with women who ran for Parliament and both won and lost. The obstacles they faced and their main goals for office are considered against the type of candidate women wished to be. Engaging with women’s groups adds another dimension of consideration. Women’s groups began to form and become active in politics around 2000 and continue to organize and call for quotas. This research considers the relationships women’s groups have with the state as well as female candidates in Egypt. I question why women’s groups consistently call for quotas for women in politics by asking about various initiatives and programs undertaken on behalf of female politicians. Reasoning as to why women’s groups call for quotas is considered against the global framework of women’s human rights and domestic Egyptian policy. This research focuses the main actors who engage with women’s rights through calling for a quota for women in national decision making bodies. These questions are asked and considered in two politically and ideologically different regimes. The changing nature of the regime allows for a broader discussion of ideological difference in order to understand why women continuously lobby the government for the use of a quota in politics.